Hubungan Daya Terima Makanan dan Tingkat Konsumsi Energi, Protein Dengan Status Gizi Pada Lansia di Panti Sosial Tresna Werdha Minaula Kendari - Rofiqoh, Rofiqoh; La Banudi, La Banudi; Buna, Pertiwi Sari (Jurnal Gizi Ilmiah, 2018)
Background : Nutritional status is influenced by several factors, one of which is food intake. If the main consumption is energy and protein, it does not meet the adequacy needed by the body, it will cause poor nutritional status, and if it lasts a long time it will cause poor nutritional status. This condition can also cause a decrease in the immune system. The acceptability of the food served is influenced by two aspects, namely the appearance of the food and the taste of the food. Objective: This study aims to determine the relationship between food acceptance and the level of energy and protein consumption with nutritional status in the elderly at the Tresna Werdha Social Institution, Minaula Kendari. Methods: This research is a descriptive analytical study with a cross sectional approach with a sample of 49 people. This research was conducted on 10 October – 14 November 2016. The independent variables included food acceptance, energy consumption level, protein consumption level and nutritional status as the dependent variable. Data on food acceptability, level of energy consumption and level of protein consumption were obtained by interview using an organoleptic test form and a 2 x 24 hour recall form, nutritional status data were obtained by measuring height and weight. Results: The study showed that most of the food acceptance was in the good category 89.8%, the energy consumption level was mostly in the sufficient category 69.4%, the protein consumption level was mostly in the less category 67.3% and the nutritional status was mostly in the poor category. normal 75.5%. There is a relationship between food acceptance and nutritional status with a value (p = 0.010), there is no relationship between energy consumption and nutritional status with a value (p = 0.298), there is no relationship between protein consumption and nutritional status with a value (p = 0.140). Conclusion: There is a relationship between food acceptance and nutritional status, there is no relationship between energy consumption and protein consumption with nutritional status